Популяції Iris sibirica L. у Криму - Podorozhniy, D.S. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
The results of the study of Iris sibirica L. coenopopulations in the Crimean Mountains are elucidated. The Iris sibirica localities in the peninsula are supposed to be an exclave in the whole area. The coenotic conditions of localities, spatial and age structures of coenopopulations, morphometric parameters of Iris sibirica specimens are presented.